(untitled) (Cardiovascular Journal, 2015)
Background: In epidemiological studies and clinical trials renal function has been shown to be an independent predictor of coronary artery disease (CAD). We conducted this study to find out the association between creatinine clearance rate (CCr) and coronary angiographic severity in patients with (CAD). Method: It was a cross sectional study carried out in the department of Cardiology, Dhaka Medical College Hospital, Dhaka during the period of April, 2011 to March, 2012. All the patients with Ischaemic heart disease (IHD) admitted in the department of Cardiology who fulfill the inclusion and exclusion criteria and underwent coronary angiogram were taken as sampling population. Sampling technique was purposive and sample size was 118. By Cockcroft-Gault formula, CCr was estimated from serum creatinine. Coronary angiographic severity of coronary artery disease was assessed by vessel score and stenosis score. Statistical analysis was carried out by descriptive statistics, correlation coefficient test and one way ANOVA test. Level of significance was set at 0.05. Results: Mean CCr among study subjects was 72.57 ± 17.78 ml/min. Vessel score showed 18.6% had normal coronaries, 37.3% single vessel disease, 31.4% double vessel disease and 12.7% triple vessel disease. There was significant positive relationship between serum creatinine and vessel score, and also negative relationship between CCr and vessel score. The study also showed significant negative correlation between CCr and stenosis score. Conclusion: Angiographic severity of coronary artery disease is associated with degree of renal dysfunction. Decreased creatinine clearance is associated with more extensive CAD. DOI: http://dx.doi.org/10.3329/cardio.v7i2.22257 Cardiovasc. j. 2015; 7(2): 108-113